The evolution from protein chemistry to proteomics : - Lundblad, Roger L. (Taylor & Francis, 2006)
Largely driven by major improvements in the analytical capability of mass spectrometry, proteomics is being applied to broader areas of experimental biology, ranging from oncology research to plant biology to environmental health. However, while it has already eclipsed solution protein chemistry as a discipline, it is still essentially an extension of classical protein chemistry, owing much of its maturation to prior contributions. Unfortunately, this debt is not always evident in current literature.